2006
DOI: 10.1093/ps/85.12.2195
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Protein Level and Total Sulfur Amino Acid:Lysine Ratio on Egg Production Parameters and Egg Yield in Hy-Line W-98 Hens

Abstract: A 3 x 3 treatment arrangement varying in dietary protein and TSAA:Lys was used to evaluate the effect of low-protein diets fed to Hy-Line W-98 laying hens. Phase I was 20 to 43 wk of age with 18.9, 17.0, and 14.4 g of protein/hen per day and 0.97, 0.85, and 0.82 TSAA:Lys, whereas phase II was 44 to 63 wk of age with 16.3, 14.6, and 13.8 g of protein/hen per day and 0.92, 0.82, and 0.72 TSAA:Lys. Egg production and feed consumption decreased from 83.7 to 82.2% and 98.8 to 95.6 g, respectively. Feed efficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
66
5
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 24 publications
26
66
5
10
Order By: Relevance
“…Similarly, did not obtain differences in yolk protein by increasing the concentration of the same amino acid in the diet. However, the current result agrees with Novak et al (2006), who observed an inverse relationship when reduced the amino acid in the diet, and reported increasing of protein content, according to reduction of dietary lysine concentration.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, did not obtain differences in yolk protein by increasing the concentration of the same amino acid in the diet. However, the current result agrees with Novak et al (2006), who observed an inverse relationship when reduced the amino acid in the diet, and reported increasing of protein content, according to reduction of dietary lysine concentration.…”
Section: Resultssupporting
confidence: 92%
“…Increasing zinc in the diet resulted in a reduction of 21% in mineral deposition. As noted by Park et al (2004) and Hudson et al (2005), in excess, zinc has detrimental effect on egg production, affecting the absorption of nutrients, and causing lesions in the pancreas and gizzard of laying hens. The greatest apparent need of lysine, under high concentration of zinc in the diet, does not correspond to increased efficiency in the use of amino acid by the bird, and then the absorption is probably affected, as shown by the data on production and egg composition.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Methionine is the first limiting AA in hens fed corn-or sorghum-and soybean meal-based diets (Cortes et al, 2001;Novak et al, 2006;Saki et al, 2012). An important aspect of the Met requirement is that this AA and Cys contain sulfur in their structure, and within the body, under conditions of deficiency of Cys, Met can be used to synthesize one molecule of Cys.…”
Section: Requirement Of Digestible Sulfur Amino Acids In Laying Hens mentioning
confidence: 99%
“…이와는 다르게 Roberts et al (2007) (Karunajeewa, 1972;Masahiro et al, 1999;Morihiro et al, 2001), 많은 연구에서 xanthophyll 함량이 높을수 록 난황 내 더욱 많은 색소들이 침착되어 짙은 색을 보인다 고 하였다 (Karunajeewa, 1972;Liu et al, 2004;Prochaska et al, 1996). 또한, 옥수수는 대체로 20∼25 mg의 xanthophyll 을 함유하고 있으며 (Sikder et al, 1998) (Khajali et al, 2007;Novak et al, 2006;신 등, 1989). 그러 나 난각 두께 및 강도를 제외한 전반적인 난각 품질에 있어 서 조단백질 수준이 낮을수록 품질이 떨어진다는 보고도 있 으며, 이것은 사료 내 TSAA : Lys 비율 차이에 기인한 것이 라 하였다 (Keshavarz and Nakajima, 1995;Keshavarz and Jackson, 1992;Leeson and Caston, 1997 …”
unclassified